Republicanism : a theory of freedom and government - Pettit, Philip, 1945- (Oxford political theory., 1997)
Pettit presents a republican alternative to the liberal and communitarian theories that have dominated political philosophy in recent years, and looks at the implications of this theory for the relation between state and civil society.